The Place and Importance of Op Art In Graphic Design Education With Its Interdisciplinary Art Education - İnceağaç, Muhammet; Tuna, Serdar (Kastamonu Egitim Dergisi, 2022)
Purpose: The aim of the research is to reveal graphically the convertibility of the Op Art movement into graphic design studies by students and how this transformation is interpreted. Methodology: In this study, the ‘Op Art’ movement from Contemporary Art was preferred as an imaginary resource in graphic design education. The research was conducted in the form of action research, one of the qualitative research methods. The research is characterized as participatory action research, one of the types of action research. The research is limited to the 2nd year students studying at Kastamonu University Kastamonu Vocational School Design Department Graphic Design Program in 2016-2017, 2017-2018, and 2018-2019. The study was conducted with 458 students who took ‘Visual Design, Publication Graphics and Typography’ courses between in the specified academic years. Since it is not possible to include all student studies, 6 student studies have been included as an example. Student studies were analyzed descriptively. Findings: As a result of the study, it was observed that the students were able to transform the Op Art movement into graphic design products, to interpret different types of works from a subjective point of view by considering the characteristics of the movement, and to create original graphic design works suitable for the composition they wanted to design. Highlights: Contemporary Art, which is covered in the chronology of art history, emerges as one of the most fundamental disciplines in art and design theoretically. It is very important to benefit from different disciplines in graphic design education, to increase the interest in design courses, and to reveal original and creative designs. From this standpoint, it can be assumed that Contemporary Art can be one of the richest resources to be used in terms of art and design. In this study, Op Art art movement, one of the Contemporary Art movements, was used in terms of creating a resource for graphic design education courses.
Keywords: Education; Art Education; Graphic Design Education; Interdisciplinary Design Education; Contemporary Art; Op Art; Eğitim Üzerine Çalışmalar; Studies on Education; 4. Education